2020
DOI: 10.35848/1347-4065/ab6b70
|View full text |Cite
|
Sign up to set email alerts
|

van der Waals epitaxy of ferroelectric ε-gallium oxide thin film on flexible synthetic mica

Abstract: This study demonstrates the formation of the van der Waals epitaxy of the ε-gallium oxide (Ga 2 O 3 ) thin film on cleaved synthetic mica via mist chemical vapor deposition. Orthorhombic ε-Ga 2 O 3 (001) was epitaxially grown on synthetic mica (001). The analysis using transmission electron microscopy revealed an in-plane orientation of ε-Ga 2 O 3 [010] || synthetic mica [010]. However, the most thermodynamically stable β-Ga 2 O 3 was grown at the film-substrate interface. The optical direct bandgap of the ε-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…This could be an indication that an interlayer could be needed in order to accommodate the substrate-layer strain. The presence of a b-Ga 2 O 3 buffer layer was observed also in the recent reports of e-Ga 2 O 3 layers on ITO/YSZ(111) 87 and of van der Waals epitaxy of e-Ga 2 O 3 on synthetic mica, 95 both via mist-CVD. In particular, the van der Waals epitaxy report of e-Ga 2 O 3 might hint at the fact that, in conditions with very weak chemical bonding between the substrate and epilayer, the growth of an initial layer of the most thermodynamically stable material in the b phase is needed, before obtaining epitaxial e-Ga 2 O 3 .…”
Section: Substrate and Lattice Matchsupporting
confidence: 70%
“…This could be an indication that an interlayer could be needed in order to accommodate the substrate-layer strain. The presence of a b-Ga 2 O 3 buffer layer was observed also in the recent reports of e-Ga 2 O 3 layers on ITO/YSZ(111) 87 and of van der Waals epitaxy of e-Ga 2 O 3 on synthetic mica, 95 both via mist-CVD. In particular, the van der Waals epitaxy report of e-Ga 2 O 3 might hint at the fact that, in conditions with very weak chemical bonding between the substrate and epilayer, the growth of an initial layer of the most thermodynamically stable material in the b phase is needed, before obtaining epitaxial e-Ga 2 O 3 .…”
Section: Substrate and Lattice Matchsupporting
confidence: 70%
“…In the Ga 2 O 3 (122) scan result in Figure c, 12-fold symmetry is evident over the 360° range, indicating the orthorhombic structure rather than the hexagonal structure (so-called ε-phase). , The in-plane rotational symmetry difference between β-Ga 2 O 3 (−401) and κ-Ga 2 O 3 (122) could also be viewed in SI Figure S1c in the SI. It has been reported that in orthorhombic Ga 2 O 3 film grown on various substrates, intermediate β-Ga 2 O 3 film could appear at the interface. , If the detection limit of the XRD scan for ultrathin films is to be considered and an interfacial ultrathin β-Ga 2 O 3 is assumed to be present, this ultrathin film would not affect the PD performance.…”
Section: Resultsmentioning
confidence: 99%
“…We observed slightly higher resistance and Schottky behavior of exfoliated n-Ga 2 O 3 +etching sample compared with the as-grown n-Ga 2 O 3 /mica. This phenomenon could be attributed to (i) material quality difference between the top n-Ga 2 O 3 layer and exfoliated bottom n-Ga 2 O 3 , which may contain polycrystal interfacial layer, 46,47 and (ii) plasma damages after Ar dry etching. 48,49 The vdW-bond-assisted exfoliation demonstrated in this work could be employed to fabricate vertical configuration Ga 2 O 3 devices, including PDs, Schottky barrier diodes (SBD), PN diode, and bottom-gate transistors.…”
Section: Resultsmentioning
confidence: 99%